1997
DOI: 10.1063/1.366115
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave initiation of the Ti5Si3 reaction in elemental powders

Abstract: Elemental powder mixes were subjected to plane-wave shock processing which reduced the initial porosity to essentially zero. Two powder mixes in a 5:3 Ti:Si atomic ratio were used: Ϫ325 mesh Ti and Si ͑Ͻ45 m͒, and Ϫ100 mesh Ti and Si ͑Ͻ150 m͒ with shock pressures up to 7.3 GPa and shock energies up to 671 J/g. Shock pressures were calculated using hugoniot parameters for porous elemental powder mixtures and shock energies were taken to be the work done by the shock ( P⌬V/2). Shock energy thresholds for complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1998
1998
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…58 The JWL equation of state was used for the explosives with the parameters obtained from the output of thermodynamic equilibrium calculations using Cheetah 2.0. Qualitatively, the same features as discussed by Vreeland et al 3 were observed in the simulation results for the current test setup, namely that the shock speed is greater in the capsule walls than in the sample, so that when no polycarbonate window is used, the wall precursor shock converges at the charge axis under the sample shortly before or shortly after the shock in the sample reflects off the steel/ sample interface. This precursor resulted in radial loadings and the convergence at the charge axis caused non-negligible shock pressures in the sample.…”
Section: E Shock Loading Characterizationsupporting
confidence: 69%
See 1 more Smart Citation
“…58 The JWL equation of state was used for the explosives with the parameters obtained from the output of thermodynamic equilibrium calculations using Cheetah 2.0. Qualitatively, the same features as discussed by Vreeland et al 3 were observed in the simulation results for the current test setup, namely that the shock speed is greater in the capsule walls than in the sample, so that when no polycarbonate window is used, the wall precursor shock converges at the charge axis under the sample shortly before or shortly after the shock in the sample reflects off the steel/ sample interface. This precursor resulted in radial loadings and the convergence at the charge axis caused non-negligible shock pressures in the sample.…”
Section: E Shock Loading Characterizationsupporting
confidence: 69%
“…Factors that have been found to influence the shock sensitivity of a reactive powder mixture include: powder morphology and particle dimensions, 1-5 stoichiometry, 2 porosity of the mixture, 3,5,6 and mechanical activating techniques such as arrested ball-milling. 6,7 Although there appears to have been little systematic study on the effect of the relative impedance and/or strength between the two components on their reactivity, it is usually considered that materials with similar impedances and yield strength would mix more intimately and react more readily.…”
Section: Introductionmentioning
confidence: 99%
“…The shock initiation of heterogeneous reactive powder mixtures via the recovery of shocked samples contained in steel capsules has been studied extensively. It is known that the shock sensitivity of a reactive powder mixture can be increased by controlling: powder morphology and particle dimensions [1][2][3][4], atomic ratio [2], porosity of the mixture [3,5], and mechanical activating techniques such as arrested ball-milling [5,6]. Despite this progress, many issues remain unresolved and a thorough understanding of the shock initiation process is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The shock speed is greater in the capsule walls than in the sample, so that when the diameter of the sample is smaller than that of the shock-generating device (this configuration will hereafter be referred to as the "narrow sample" setup), a precursor shock travels along the edges of the sample and converges at the charge axis under the sample shortly before or shortly after the shock in the sample reflects off the bottom steel/sample interface. This precursor results in radial loadings and its convergence at the charge axis causes non-negligible shock pressures in the sample (see, for instance, [3]). The reflected shock at the bottom of the sample and the convergence of the precursor shock under the sample may also result in large pressure (and temperature) increases.…”
Section: Introductionmentioning
confidence: 99%
“…Shock wave initiation of the Ti 5 Si 3 reaction in porous mixture 5:3 Ti:Si atomic ratio was considered by Vreeland et al [26]. It was experimentally found that critical shock energy for complete reaction depends upon powder particle size and the initial porosity of powder.…”
Section: Introductionmentioning
confidence: 99%